Relationship of the Severity of Maxillofacial Trauma Based on Facial Injury Severity Scale (FISS) Against the Severity of Head Injury - Ary Rachmanto; Abda Arif (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2019)
ABSTRACT Introduction. Facial bone fractures can be accompanied by life-threatening complications such as head injuries. Maxillofacial trauma increases with time. The maxillofacial facial injury severity scale (FISS) scoring system was introduced to assess the patient's severity, prognosis, and outcome. Maxillofacial FISS has predictive value on the severity of head injuries. Method. This research uses analytic observation method with cross sectional design approach. The population and sample were all maxillofacial trauma patients who had been treated at RSUP dr. Moehammad Hoesin Palembang from January-September 2018. Data is taken from secondary data, namely the patient's medical record. Results. The incidence of maxillofacial trauma at RSUP dr. Moehammad Hoesin Palembang is 95 cases. The most cases occurred in the age group <30 years (62.1%). Gender male (85.3%), the scene outside the city (52.6%). There were 21 maxillofacial trauma patients undergoing neurosurgery (22.1%). There was no relationship between FISS and the severity of head injury (p = 0.063), there was a significant relationship between FISS and neurosurgery (p = <0.001). Conclusion. There is a relationship between the severity of maxillofacial trauma based on the Facial Injury Severity Scale (FISS) score on the severity of the head injury.